Flood Discharge Analysis Using the SCS Hydrograph Method in the Krung Tripa Watershed - Maulida Bunga Azzura; Astiah Amir; M. Faisi Ikhwali (Litbang Pemas - Universitas Islam Lamongan, 2022)
The purpose of this study was to analyze the flood discharge of the Krung Tripa river return period and flood behavior based on hydrographic data obtained from rainfall data and estimate the magnitude of peak flood discharge. Flooding is the main problem caused by the overflow of Krung Tripa, with administrative Krung Tripa passes through 2 (two) districts in Aceh Province. Several factors cause flooding, including slope factors or topography of an area, soil type, and land uses. The method used to analyze flood discharge is the SCS Hydrograph method using secondary data. The results of flood discharge analysis obtained flood discharge plans with 2-year return period for 2464.033 m3/s, 5-year return period for 3597.893 m3/s, 10-year return period for 4372.634 m3/s, 25-year return period for 5377.98 m3/s, 50-year return period for 6153.054 m3/s, 100-year return period for 6946.462 m3/s.